Assessment and Diagnosis of the water resources carrying capacity in the Huaihe River basin of Anhui Province - Hui Zhang; Tianru Ma; Zhengwei Pan; Lan Yang; Dejian Wang; Guangye Yu; He Li; Kezhi Zhang (Ecological Indicators)
This study aims to expand the evaluation theory and application methods of water resources carrying capacity (WRCC) and to measure regional WRCC in multiple dimensions. To this end, a WRCC evaluation system based on a system perspective is proposed. This system is divided into three subsystems, comprising 23 key indices. By combining the Improved Coefficient of Variation Method (ICVM) with the Improved Analytic Hierarchy Process (IAHP), both the subjective and objective weights are calculated, effectively accounting for expert experience and data variability. Meanwhile, the Fuzzy Connection Number (FCN) method is introduced to address the uncertainties in the evaluation process. Taking the Huaihe River Basin of Anhui Province (HRBIAP) as a case study, this work conducted a WRCC evaluation across nine districts during the period from 2014 to 2022. The results show that the overall WRCC level of HRBIAP is at Ⅰ-Ⅲ, with the ecological environment subsystem performing the worst. The WRCC level shows a fluctuating upward trend. Cities in the northeastern and southwestern have higher WRCC rating. In contrast, the northwestern region has more barriers than the southeastern region, although the number of barriers in the northwestern region is decreasing. Therefore, there is an urgent need to strengthen ecological environmental management, such as increasing the amount of ecological water replenishment and utilizing recycled water. This study can promote the development of water resources research and provide an effective guarantee for regional WRCC assessment and development.